2015
DOI: 10.1007/s10120-015-0535-7
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastasis risk according to the depth of invasion in early gastric cancers confined to the mucosal layer

Abstract: EGCs invading the MM had a higher rate of lymph node metastasis than those confined to the LP. Further study is needed to evaluate whether different curative treatment criteria are needed for LP-confined and MM-invading EGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…In recent years, there has been controversy over whether ulcers are associated with LNM. [22][23][24] Few previous studies have assessed the risk of LNM in ulcerative EGC alone, but some researchers have investigated selected cases. A metaanalysis showed that, according to the expanded criteria for ESD, differentiated mucosal lesions \ 30 mm with ulceration were associated with a minimal risk of LNM.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been controversy over whether ulcers are associated with LNM. [22][23][24] Few previous studies have assessed the risk of LNM in ulcerative EGC alone, but some researchers have investigated selected cases. A metaanalysis showed that, according to the expanded criteria for ESD, differentiated mucosal lesions \ 30 mm with ulceration were associated with a minimal risk of LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EGCs with LNM were found to be more in submucosa invasion and LVI in our study. Besides them, tumor differentiation and histologic types have been demonstrated to predict the likelihood of LNM [ 28 , 29 ]. However, in our study, we failed to found significant differences in the rate of LNM among them, although this trend still existed.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of lymph node metastasis was closely related to depth of invasion (3,4). In T1 stage GC, the lymph node metastasis rate was relatively low and D1 or D1 + lymphadenectomy was enough for such patients (1,5,6). For tumors with serosa invasion, more extended lymph node dissection, such as D2 or D2+ was required as the high incidence of lymph node metastasis (7-13).…”
Section: Introductionmentioning
confidence: 99%